2015
DOI: 10.3122/jabfm.2015.05.150024
|View full text |Cite
|
Sign up to set email alerts
|

Success in the Achieving CARdiovascular Excellence in Colorado (A CARE) Home Blood Pressure Monitoring Program: A Report from the Shared Networks of Colorado Ambulatory Practices and Partners (SNOCAP)

Abstract: Background: Blood pressure (BP) control among primary care patients with hypertension is suboptimal. Home BP monitoring (HBPM) has been shown to be effective but is underused.Methods: This study was a quasi-experimental evaluation of the impact of the A CARE HBPM program on hypertension control. Nonpregnant adults with hypertension or cardiovascular disease risk factors were given validated home BP monitors and reported monthly average home BP readings by Internet or phone. Patients and providers received feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The community advisory council worked in an iterative process to “translate” health care promotions into public service messages that would be understandable to the lay community [ 23 ]. In accompanying articles, this approach was found to have positive results in several distinct interventions and was associated with statistically significant increased self-reported intention to engage in colorectal cancer screening [ 24 ], increased use of asthma inhalers as well as asthma action plans [ 25 ], and improved blood pressure control rates [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The community advisory council worked in an iterative process to “translate” health care promotions into public service messages that would be understandable to the lay community [ 23 ]. In accompanying articles, this approach was found to have positive results in several distinct interventions and was associated with statistically significant increased self-reported intention to engage in colorectal cancer screening [ 24 ], increased use of asthma inhalers as well as asthma action plans [ 25 ], and improved blood pressure control rates [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some providers cited concerns over accuracy of data as a potential road block to using home BP monitors on a wider scale (n=4) [14,42-44]. Another barrier to provider adoption was the lack of evidence or proof that DHTs improved patient outcomes (n=3) [32,38,45].…”
Section: Resultsmentioning
confidence: 99%
“…These control rates are similar to the 6-to-12-month hypertension control rates of 54% to 71% noted in 4 HBPM studies using telemonitoring with independent pharmacist comanagement 18,19,46,47 and the 53% 12-month control rate in a study without telemonitoring that used direct HBPM feedback to primary care clinicians. 48 Primary care clinicians have expressed several concerns about implementing AOBP and HBPM in a nonresearch setting: whether an AOBP/HBPM program can be efficiently incorporated into daily clinical practice; whether patients will follow through with HBPM despite its substantial time/ effort commitment; and whether patients will perform HBPM with sufficient accuracy. 14,49 With respect to the first concern about clinic efficiency, 68% of our clinic staff reported that the AOBP/ HBPM program positively affected hypertension management and did not require excessive time/ effort, an interpretation supported by the estimated time commitments noted in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Prior HBPM studies note that up to 20% of patients decline to initiate HBPM 18 and report rates of submission of HBPM results of 70% to 91% with dedicated pharmacist support 46,47 but as low as 32% to 36% when such support was unavailable. 27,48 Studies are needed to determine which patients are more likely not to complete HBPM and whether directed intensive patient education and shared decision making can minimize this barrier.…”
Section: Discussionmentioning
confidence: 99%